A novel polyoxovanadate-based Co-MOF: highly efficient and selective oxidation of a mustard gas simulant by two-site synergetic catalysis. Issue 25 (17th June 2020) - Tian, Hong-Rui; Zhang, Zhong; Liu, Shu-Mei; Dang, Tian-Yi; Li, Xiao-Hui; Lu, Ying; Liu, Shu-Xia
Abstract : A polyoxovanadate-based cobalt organic framework (V–Co-MOF) was synthesized and it, as a heterogeneous catalyst, can catalyze the rapid selective oxidation of a mustard gas simulant to a non-toxic product by the two-site synergistic effect of V V and Co II . Abstract : Two novel polyoxovanadate-based metal–organic frameworks (MOFs), [Co(bib)]V2 O6 (V–Co-MOF) and [Ni(en)(bib)]V2 O6 ·2H2 O (V–Ni-MOF) (bib = 1, 4-bis(1 H -imidazoly-1-yl)benzene, en = ethylenediamine) were facilely synthesized under mild hydrothermal conditions. Single-crystal X-ray diffraction analysis shows that the V sites in both compounds adopt VO4 tetrahedral coordination geometries, and the Co center in the V–Co-MOF presents a four-coordinated distorted tetrahedron configuration (coordinatively unsaturated metal sites, CUMS), while the Ni center in the V–Ni-MOF exhibits six-coordinated octahedral geometry (coordinatively saturated metal sites, CSMS). Given that the CUMS can generally be used as active sites for catalytic reactions, we explored the catalytic activities of these two compounds for the oxidation of a mustard gas simulant, 2-chloroethyl ethyl sulfide (CEES). The experimental results indicate that they can catalyze the oxidation of CEES to give the only nontoxic product, 2-chloroethyl ethyl sulfoxide (CEESO). Significantly, the V–Co-MOF exhibits higher catalytic activity; it converts 100% of CEES in 10 min, whereas V–Ni-MOF converts only 47.5% of CEES under identical conditions. Researching the mechanism of the catalytic reaction revealed that the excellent catalytic performance of the V–Co-MOF was attributed to the two-site synergetic effect: (1) the oxidant H2 O2 interacts with the V site to produce peroxovanadium with higher oxidation activity; (2) the S atom in CEES coordinates with the four-coordinated Co(ii ) center to obtain 2-chloroethyl ethyl sulfonium cation (CEES+), which makes the CEES more easily oxidize to CEESO based on the oxidation mechanism of peroxovanadium and shortens the molecular size distance between CEES and the obtained peroxovanadium, thereby greatly improving the rate of the catalytic reaction. To our knowledge, this is the first dual-active-site polyoxometalate-based MOF catalyst for catalysing the oxidative detoxification of CEES.